2021
DOI: 10.1186/s12888-021-03414-9
|View full text |Cite
|
Sign up to set email alerts
|

Individualized diagnosis of major depressive disorder via multivariate pattern analysis of thalamic sMRI features

Abstract: Background Magnetic resonance imaging (MRI) studies have found thalamic abnormalities in major depressive disorder (MDD). Although there are significant differences in the structure and function of the thalamus between MDD patients and healthy controls (HCs) at the group level, it is not clear whether the structural and functional features of the thalamus are suitable for use as diagnostic prediction aids at the individual level. Here, we were to test the predictive value of gray matter density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 75 publications
2
10
0
Order By: Relevance
“…The thalamus might be a proper biomarker of MDD that could be used to predict patients’ antidepressant treatment responses. Our previous study and many other thalamic imaging studies have found thalamic abnormalities in patients with MDD, and these results show that the thalamus may play an important role in MDD ( Li et al, 2021 ). Whether the thalamus is related to the prognosis of depression has also attracted the attention of researchers.…”
Section: Introductionsupporting
confidence: 67%
See 4 more Smart Citations
“…The thalamus might be a proper biomarker of MDD that could be used to predict patients’ antidepressant treatment responses. Our previous study and many other thalamic imaging studies have found thalamic abnormalities in patients with MDD, and these results show that the thalamus may play an important role in MDD ( Li et al, 2021 ). Whether the thalamus is related to the prognosis of depression has also attracted the attention of researchers.…”
Section: Introductionsupporting
confidence: 67%
“…The participants’ GMV, GMD, ALFF, and fALFF values in the thalamus were extracted as regression and classification features. More information were the same as previously reported ( Li et al, 2021 ).…”
Section: Methodsmentioning
confidence: 90%
See 3 more Smart Citations